A sombra do objeto e o trabalho estético da melancolia - Dias, Reginaldo Rodrigues (2024)
The objective of this thesis is to relate Freud's concept of the shadow of the object with the notion of melancholic work, considering the latter as an aesthetic work between lucidity and the dark present in the discourse of melancholy. The occurrence of the emergence of this concept shows how important the discussion between Freud and his contemporaries was for its emergence, especially with regard to the concepts of identification and narcissism that together form the expression narcissistic identification, so important for understanding the mechanism of constitution of melancholy. The notion of the object's shadow gains a broader conceptual body in the work of current psychoanalysts, based on which it was possible to understand the shadow as a primitive sediment, first removed from the other, its pre-specular mark, therefore, the shadow as a precursor of image. We developed the idea that the shadow both represents what remained of the object after the loss, and also delimits, in a rudimentary and, we can say, pre-symbolic way, its absence. Considering the delusion of self-accusation as a central specific that expresses the dark covering of the object over the self, its origins in psychiatry and the pre-psychoanalytic period go back to the concepts of assimilatory delusions that seek to explain the patient's state and the subjugation of the self as its failure. process of reorganization of the world. In this sense, to the extent that it is possible to describe oneself in detail, the imagetic deficiency of the self finds in delirium a profusion of faded images that gain brilliance in the aestheticization of discourse. It is concluded that the work of aestheticizing the speech with words, whose ornamental character is exalted, acts between the light, represented by melancholic lucidity, and the shadow of its alienation, thus causing the deflection of the object's shadow and allowing a contour clear for the self and consequently for the other, in melancholy.